Analisis Framework Stimulus Organism Response (SOR) Pada Live Streaming Marketplace Terhadap Keputusan Pembelian Di LAF Project - Janah, Nisa Raudatul; Istiqomah, Yuliani; Setiawati, Liya (Innovative: Journal Of Social Science Research, 2024)
This study analyzes the influence of marketplace live streaming on purchasing decisions using the Stimulus-Organism-Response (SOR) framework on LAF Project, a shoe retail company. Utilizing a quantitative survey method, data was collected from 45 respondents who are followers of LAF Project's Shopee account. This research focuses on three main factors: Store Atmosphere, Online Customer Reviews, and Online Customer Ratings, to understand how the stimulus from live streaming affects consumers' perceptions and purchasing decisions. The results show that Store Atmosphere and Online Customer Reviews have a significant positive influence on purchase decisions, with Store Atmosphere showing a stronger influence. In contrast, Online Customer Ratings showed a negative influence on purchase decisions, indicating that other factors may play a role in moderating the influence of ratings on consumer decisions. This study confirms the importance of SOR elements in influencing consumer behavior on live streaming platforms and the implications for digital marketing strategies.